Numerical Analysis of Microcracks of Fly Ash/Slag Concrete with Cobble as Coarse Aggregate - Songfang Xie; Mingxing Gao; Hangtian Li (Advances in Materials Science and Engineering)
In order to improve mechanical properties of fly ash/slag concrete with large size cobble as coarse aggregate, this paper analyzes the effect of different factors on the concrete through the flexural strength test. The Monte Carlo simulation is used in the finite element solver of ANSYS to conduct the four-point bending beam test. Three-dimensional and two-dimensional finite element models are established to discuss how the gradation of large size cobbles affects the performance of the concrete by comparing macromechanical experiments. Results show that the gradation of large size cobbles is the main factor affecting the performance of the concrete. Slag generates the least effect on the concrete with cobble as coarse aggregate. When the mixing amount of slag and fly ash is 10%, the concrete presents the best flexural performance. Through the numerical loading test of the two-dimensional model for fly ash/slag concrete with cobble as coarse aggregate, it can be concluded that the change of the concrete follows the law of macromechanical properties.